Comparison of the efficacy between bilateral proximal tubal occlusion and total salpingectomy on ovarian reserve and the cholinergic system: an experimental study - Atilgan, Remzi; Pala, Sehmus; Kuloglu, Tuncay; Sanli, Cengiz; Yavuzkir, Seyda; Ozkan, Zehra Sema (Tubitak Scientific & Technological Research Council Turkey, 2020)
Background and aim: To compare the effects of bilateral proximal tubal occlusion and bilateral total salpingectomy on ovarian reserve and the cholinergic system via rat experiment. Materials and methods: Twenty-one adult female rats were randomly divided into the following three groups: G1 (n = 7), sham group; G2 (n = 7), bilateral total salpingectomy group; and G3 (n = 7), bilateral proximal tubal occlusion group. Four weeks later, the abdomen of the rats was opened. The right ovarian tissues were stored in 10% formaldehyde, whereas the left ovarian tissues were stored at -80 degrees C in aluminum foil. Serum samples were evaluated for antimullerian hormone. The right ovary was used for histological and immunoreactive examination, and the left ovary was used for tissue MDA analysis. Tissue samples were analyzed for MDA levels with spectrophotometric measurement, apoptosis with TUNEL staining, fibrosis score with Mason trichrome staining, ovarian reserve with HE staining, and cholinergic receptor muscarinic 1 (CHRM1) level with immunoreactivity method. Results: Compared to G1 and G3, the number of corpus luteum with secondary follicles was significantly lower in G2, whereas the number of ovarian cysts and fibrosis and apoptosis scores increased significantly. The CHRM1 immunoreactivity was significantly lower in G2 than in G1 and G3. Conclusions: Compared to the bilateral proximal tubal occlusion performed by using bipolar cautery, bilateral total salpingectomy in rats leads to a significant damage in ovarian histopathology and the cholinergic system.
Keywords: Ovarian reserve; proximal tubal occlusion; CHRM1; rat